Characterization of nanostructured mn-zn ferrites synthesized by coprecipitation method using ctab - Maranhão, W. C.A.; Ichikawa, R. U.; Turrillas, X.; Yoshito, W. K.; Saeki, M. J. [UNESP]; Orlando, M. T.D.; Martinez, L. G. (Trans Tech Publications, 2020)
In this work it was investigated the influence of CTAB surfactant concentration on the synthesis of the compound Mn0.75Zn0.25Fe2O4 by the coprecipitation method. It was also compared the influence of hydrothermal treatment on the synthesized materials. The magnetic properties were characterized by AC susceptometry for the determination of the magnetic susceptibility and magnetic density energy. The phases, crystal structure and morphology of the nanoferrites were determined by Rietveld analysis of X-ray diffraction data. It was found the presence of two phases: Franklinite and Akaganeite and it was shown that the samples synthesized only by coprecipitation presented the tendency to increasing the crystallite sizes of the akaganeite phase and decreasing of crystallite sizes of the Franklinite phase as a function of CTAB concentration. The samples submitted to subsequent hydrothermal treatment presented a tendency to decreasing the crystallite sizes of both phases and increasing in Franklinite phase fraction, compared to the samples synthesized only by coprecipitation, suggesting that the hydrothermal treatment was effective in obtaining nanostructured materials of smaller particles.
Keywords: Coprecipitation; Hydrothermal synthesis; Mn-Zn Ferrites; Rietveld Method; X-ray diffraction